1977
DOI: 10.1139/v77-582
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrole chemistry. XVI. Acylation of the pyrrolyl ambident anion

Abstract: . Can. J. Chem. 55, 4103 (1977). An investigation of the acylation of the pyrrolyl ambident anion has been carried out. The results have been rationalized in terms of the 'principle of hard and soft acids and bases.' The metal cation, solvent or complexing agent, halide of the pyrrole Grignard reagent, and temperature were varied. As well, the reactions of acylating agents of the carbonyl, cyanide, and carbimine type with the pyrrole Grignard reagent were studied to determine N/C acylation ratios under the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 16 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…In the course of our studies of pyrrole cycloaddition reactions , tetrakis‐( N ‐pyrrolyl)methane 4 has been obtained as an unprecedented product in the reaction of potassium pyrrole 5 in THF with triphosgene 6 , a scheme designed to produce N , N ′‐dipyrrolyl ketone 7 (Scheme ). This ketone has earlier been reported to be formed in low yield (4%) by the reaction of N ‐pyrrolylmagnesium bromide with ethyl chlorothiolformate; however, no formation of 4 was mentioned . Cycloaddition properties of 7 are described in the final section of this account.…”
Section: Resultsmentioning
confidence: 83%
“…In the course of our studies of pyrrole cycloaddition reactions , tetrakis‐( N ‐pyrrolyl)methane 4 has been obtained as an unprecedented product in the reaction of potassium pyrrole 5 in THF with triphosgene 6 , a scheme designed to produce N , N ′‐dipyrrolyl ketone 7 (Scheme ). This ketone has earlier been reported to be formed in low yield (4%) by the reaction of N ‐pyrrolylmagnesium bromide with ethyl chlorothiolformate; however, no formation of 4 was mentioned . Cycloaddition properties of 7 are described in the final section of this account.…”
Section: Resultsmentioning
confidence: 83%
“…It also indicated that LGE 2 could react with the guanidino group of arginine to form what we hypothesized to be bis(levuglandinyl) urea (BLU) adducts with the following combination of structures: anhydrolactam-anhydroSchiff base (anHL-anHSB, m/z 691.8), lactam-Schiff base (L-SB, m/z 727.4), and hydroxylactam-Schiff base (OHL-SB, m/z 743.5) BLU adducts (Figure 2). We hypothesized that the formation of these BLU would follow the mechanism that we present in Figure 3: after both the amino groups of the guanidine function react with LGE 2 to form pyrroles, the bond between N 6 and C 7 becomes a localized double bond (10) and undergoes nonenzymatic hydrolysis (11) to yield the corresponding BLU and ornithine.…”
Section: Identification Of Arginyl-mentioning
confidence: 99%